Upaya Peningkatan Hasil Belajar Pendidikan Pancasila Melalui Pembelajaran Aktif Tipe Think Pair and Share Siswa Kelas II SDN 23 Mataram - Nurlaili, Nurlaili; Tahir, Muhammad; Tahir, Khaerudin (Mataram University, 2025)
This study aims to improve the learning outcomes of second-grade students at SDN 23 Mataram in the subject of Pancasila Education through the implementation of the Think Pair and Share (TPS) active learning model. The research employed a Classroom Action Research (CAR) method conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of this study were 16 students. The results showed a significant improvement in students’ learning outcomes. The average score increased from 64.0 in the pre-cycle to 76.5 in Cycle I with a classical mastery level of 70%, and further increased to 86.3 in Cycle II with a classical mastery level of 94%. The application of the TPS model not only improved students’ learning outcomes but also encouraged active participation, critical thinking skills, and confidence in expressing opinions. Therefore, the Think Pair and Share model is proven effective as a learning strategy to enhance students’ understanding of Pancasila values in elementary education.